Antiplasmodium and chloroquin resistance reversing effects of selected pure phytochemicals - Ibraheem, Zaid Osamah (2017)
Malaria is a devastating parasitic multi-organ disease afflicting millions and killing thousands of people annually. Emergence of drug resistant strains of the parasite has worsened the catastrophe of its dissemination. This urged the scientists to search for safe alternatives or drugs resistance reversing agents. This study was comprised of two sections which studied the antiplasmodium and chloroquine resistance reversing effects of eleven selected phytochemicals, namely; andrographolide, embelin, mangostin, mangoferin, harmalol, harmol, harmaline, 3-aminocoumarin, scopoletin, esculetin and umbelliferone, both in vivo and in vitro. In the in vitrostudy, Plasmodium falciparum K1 and 3D7; the chloroquine resistant and sensitive strains, were used. The compounds safety was screened through comparing their potency against the mentioned parasite with that against Vero cells (mammalian cells) or intact RBCs. SYBRE-Green -1 based drug sensitivity, MTT and RBCS stability assays were used for this purpose. Isobologram technique was used to find their effect against chloroquine resistance in Plasmodium falciparum K1. Their impact on hemozoin formation was assessed through running β-haematin formation and haem fractionation assay to elucidate their molecular mechanism. Meanwhile, RBCs osmotic fragility and merozoites invasion assays were performed to assess their impact on RBCs membrane. Finally, the in vivo anti-plasmodium and chloroquine resistance reversing effects of those; which succeeded to give a safe and productive effect, in vitrowas screened using chloroquine resistant and sensitive Plasmodium berghei infected ICR mice model. The in vitrostudy showed that all the test compounds had weak to moderate anti-plasmodium effect which turned them illegible to be implemented as conventional anti-malaria drugs. Hemozoin formation was affected only by embelin, mangostin, mangoferin and 3-aminocoumarin. Unlike the others; embelin has affected the RBCs stability profoundly so it was considered to be unsuitable for this purpose while mangostin exerted milder effect. On the other hands, simple coumarins (umbeliferon, scopoletine and esculetine) produced weak antiplasmodium effect and failed to reverse chloroquine resistance. Only andrographolide, mangostin and harmaline were chosen for the in vivo study as they were the only drugs that showed optimistic outcomes in the in vitrostudy. Their effect was tested against a chloroquine resistant clone of Plasmodium berghei that was experimentally prepared through continuous exposure of the sensitive parasite to chloroquine. The study showed that mangostin and harmaline were lethal to the plasmodium infected mice in spite of their safety against the uninfected ones and in the in vitromammalian cells culture. Meanwhile andrographolide was more potent in vivo and could have reduced the extent of the disease induced damage. In conclusion, caution should be exercised while administration of herbal products in malaria patients without complete reliance on reports generated by the in vvo studies and suggests co-administration of andrographolide with chloroquine to get an additive effect